Experimental Study and Numerical Model of Spruce and Teak Wood Strength Properties Under Compressive High Strain Rate Loading - Ediansjah Zulkifli; Patria Kusumaningrum; Diah Puspita Rahmi (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Spruce and teak wood as anisotropic materials have complex behavior, particularly in the relationship between strain-rate and strength. High strain-rate compression tests between 590 s-1 and 3300 s-1 were carried out using two types of split Hopkinson pressure bar (SPHB) in order to measure the behavior of the wood along three principal axes with respect to fiber direction and growth rings. Numerical simulation using finite element software of the wood materials under high strain rates was performed and showed results with only a difference of 10% to the experimental results. The strain rate affects the strength of materials. In this case, it follows the power function, which means the higher the strain rate, the stronger the material.